Automatic Translation from Binary Object Files to Hardware Description Languages - Würstlein, Alexander (2011)
This work describes the design and implementation of a tool to automatically translate data structure descriptions, extracted from debug information embedded into object files, into hardware description languages. Existing proven technologies like DWARF and VHDL are used in novel ways, thereby tackling certain challenges in the overall context of improving non-functional properties of operating systems through the use of FPGAs. Various aspects of the usage environment, the inner workings and of further possible uses are discussed in detail. Also described are current and possible extensions to other output formats and languages and potential problems during use.